Video structure analysis for content-based indexing and categorisation of TV sports news. (1st January 2012) - Choroś, Kazimierz
Text and video seem to be totally different digital media. Nevertheless, similarly to text, video is also hierarchically structured. The knowledge of the structures of textual data as well as of video data allows for more efficient indexing. The analogies of text and video structures are observed and discussed. Next, the juxtaposition is presented of two indexing processes, i.e., of text and video indexing based on the content analysis of their structure units. Then, different possible strategies of video indexing are also considered. Several frameworks of automatic detection and content-based categorisation of video shots and scenes have already been proposed in scientific literature. The experiments mainly concern with the classification of TV news, the categorisation of the sport events in TV sports news, the detection of people or special events etc. It has been observed that many sport videos have repetitive structure patterns. In the new indexing procedures implemented in the AVI – the Automatic Video Indexer – the knowledge of the structure of video shots and scenes allowed to reduce significantly the number of frames analysed in a given process.